Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) 2/3 = 12/18 => x = 18
b) 14/56 = 1/4 => x = 4
c) 2/5 = 50/125 => x = 50
a)\(\frac{2}{3}=\frac{12}{x}\)
\(\frac{2\cdot6}{3\cdot6}=\frac{12}{x}\)
\(\frac{12}{18}=\frac{12}{x}\)
x=12
b)\(\frac{14}{56}=\frac{1}{x}\)
\(\frac{14\div14}{56\div14}=\frac{1}{x}\)
\(\frac{1}{4}=\frac{1}{x}\)
x = 4
c)\(\frac{x}{125}=\frac{2}{5}\)=
\(\frac{x}{125}=\frac{2\cdot25}{5\cdot25}\)
\(\frac{x}{125}=\frac{50}{125}\)
x = 50
1.
\(\frac{5}{3}-\frac{1}{4}+\frac{1}{3}-\frac{3}{4}\)
\(=\left(\frac{5}{3}+\frac{1}{3}\right)-\left(\frac{1}{4}+\frac{3}{4}\right)\)
\(=2-1=1\)
\(\frac{2}{7}\cdot\frac{1}{5}+\frac{2}{7}\cdot\frac{4}{5}=\frac{2}{7}\cdot\left(\frac{1}{5}+\frac{4}{5}\right)=\frac{2}{7}\cdot1=\frac{2}{7}\)
#Louis
\(1.a)\frac{5}{3}-\frac{1}{4}+\frac{1}{3}-\frac{3}{4}\)
\(=\left(\frac{5}{3}+\frac{1}{3}\right)-\left(\frac{1}{4}+\frac{3}{4}\right)\)
\(=2-1\)
\(=1\)
\(b)\frac{2}{7}\times\frac{1}{5}+\frac{2}{7}\times\frac{4}{5}\)
\(=\frac{2}{7}\times\left(\frac{1}{5}+\frac{4}{5}\right)\)
\(=\frac{2}{7}\times1\)
\(=\frac{2}{7}\)
\(2.a)\frac{5}{6}+\frac{7}{12}-\frac{2}{9}\)
\(=\frac{30}{36}+\frac{21}{36}-\frac{8}{36}\)
\(=\frac{43}{36}\)
\(b)\frac{4}{9}\times\frac{5}{8}+\frac{1}{6}\)
\(=\frac{5}{18}+\frac{1}{6}=\frac{5}{18}+\frac{3}{18}\)
\(=\frac{8}{18}=\frac{4}{9}\)
\(c)2:\frac{3}{11}-\frac{13}{12}\)
\(=2\times\frac{11}{3}-\frac{13}{12}\)
\(=\frac{22}{3}-\frac{13}{12}\)
\(=\frac{25}{4}\)
48 x X - X + 53 x X = 7900
48 x X - X x 1 + 53 x X = 7900
X x ( 48 - 1 + 53 ) = 7900
X x 100 = 7900
X = 7900 : 100
X = 79.
Vậy X = 79.
Hok tốt !
1) 1/2*1/6=1/12 ; 1/3*1/4=1/12. Ta có : 17/5+1/12*71/5-1/12*28/5=1/12*(17/5+71/5-28/5)=1/12*60/5=1/12*12=1 2)1/10+4/20+9/30+16/40+25/50 =1/10+2/10+3/10+4/10+5/10(rút gọn) =15/10=3/2 3)18/15*(2525/3636+1515/1818-2020/7272)=6/5*(25/36+5/6-5/18)(rút gọn)=6/5*25/36+6/5*5/6-6/5*5/18=5/6+1-1/3=9/6=3/2.
125x[x+3]=9871
x+3 =9871:125
x+3=78,968
x=78,968-3
x=75,968
k mik nhe
\(20+x=15\cdot2+40\)
\(20+x=30+40\)
\(20+x=70\)
\(x=70-20\)
\(x=50\)
x-(x-60)
x-x+60 = 60
=> B=60
dễ quá con này bằng có B=60